CEO overconfidence, tax avoidance, and education foundation - Kurnia Indah Sumunar; Luluul Jannah; Darlin Aulia (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2019)
Companies use tax avoidance to maximize after-tax income. This study examines whether CEO overconfidence has a positive effect to tax avoidance, and whether education foundation as a moderating variable strengthens or weakens that effect. Many studies on tax avoidance only focus on CSR activities in general and do not analyze the role of CEO in decision making. Using panel datasets from 305 companies in Indonesia from 2013-2017 that obtained from Thomson Reuters, the results show that CEO overconfidence has a significant positive effect on tax avoidance, and education foundation weakens the positive effect of CEO overconfidence on tax avoidance. With the role of CEO overconfidence, companies will do tax avoidance because CEO overconfidence can use their strong policy preferences to make decisions.